2001
DOI: 10.1034/j.1600-0722.2001.00965.x
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal study of dental caries, tooth mortality and interproximal bone loss in adults with intellectual disability

Abstract: The investigation focused on longitudinal changes of oral health in a group of adults with intellectual disability. A number of 124 individuals, aged 21-40 yr in 1990, were followed during 8.5 yr. The incidence and prevalence of caries, incidence of tooth mortality, and interproximal bone loss were registered from clinical examinations and bite-wing radiographs. The subjects visited the dental clinic for preventive dental care on average every third month during the period. The caries incidence was low, on ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
56
0
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 17 publications
2
56
0
2
Order By: Relevance
“…In recent years, the rate of extensive caries requiring pulp treatment or extraction among P/MD patients has reportedly been decreasing, indicating a decline in the severity of caries 2,3,9) . According to Morisaki 8) , the clinical polarization of patients is becoming apparent, with some, albeit few, patients presenting with advanced, severe caries affecting several teeth.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the rate of extensive caries requiring pulp treatment or extraction among P/MD patients has reportedly been decreasing, indicating a decline in the severity of caries 2,3,9) . According to Morisaki 8) , the clinical polarization of patients is becoming apparent, with some, albeit few, patients presenting with advanced, severe caries affecting several teeth.…”
Section: Discussionmentioning
confidence: 99%
“…5 A number of recent studies have demonstrated that individualized preventive dental care, performed regularly using generally available methods and assistance with maintaining adequate oral hygiene are effective for suppressing the severity and progression of periodontal disease in Down syndrome patients. [18][19][20][21] However, as is evident from this case study, the wide variance in the degree of intellectual impairment and the development of complex medical histories may present significant barriers to achieving and maintaining oral health. 19 Severe odontogenic infection is potentially a lifethreatening event and "management is primarily surgical with skilled anaesthetic airway management".…”
Section: Discussionmentioning
confidence: 99%
“…However, the prevalence of dental caries among Down syndrome individuals is generally considered to be low compared to different control groups, with those individuals residing in institutions generally having a lower caries experience than those residing at home. [15][16][17][18] The reasons for this observed lower caries rate are varied and may include low levels of S. mutans found in the saliva, genetic or environmental factors. 16,17 The increased prevalence of periodontal disease among people with Down syndrome compared to age matched groups of both non-Down syndrome and other people with intellectual disability is well documented.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown that a different salivary environment of electrolytes and pH is manifested in DS children, leading to the lower reported caries rate (Davidovich et al, 2010) 3.2 Periodontal disease DS individuals usually present with poor oral hygiene and manifested as marginal gingival inflammation, acute and subacute necrotizing gingivitis, advanced chronic periodontitis, loss of attachment in form of gingival recession and increased pocket depth, alveolar bone loss, suppuration or even abscesses, furcation involvement in the molars, increased tooth mobility, and even loss of teeth (Shaw & Saxby, 1986) (Figures 5B & 6). DS individuals had a prevalence of 60 to 90% percent and increased severity of periodontal disease compared with normal age-matched controls and subjects with other mental disabilities of similar age (Cutress, 1971b;Orner, 1976;Barnett et al, 1986;Reuland-Bosma & van Dijk, 1986;, Modeer et al, 1990;Shapira et al, 1991;Ulseth et al, 1991;Desai, 1997;Gabre et al, 2001;Lopez-Perez et al, 2002;Sakellari et al, 2005;Cheng et al, 2007;Khocht et al, 2010). Obviously the severity of periodontal disease among DS individuals is milder in recent years' reports as better dental care have been employed to take care of them early in their life.…”
Section: Dental Cariesmentioning
confidence: 99%
“…Low prevalence of dental caries or tooth decay in both primary and permanent dentitions of DS individuals has been widely reported (Cutress, 1971a;Orner, 1975;Barnett et al, 1986;Vigild, 1986;Ulseth et al, 1991;Gabre et al, 2001;Bradley & McAlister, 2004;Cheng et al, 2007;Dellavia et al, 2009;Davidovich et al, 2010). Cutress (1971a) examined 416 DS subjects and found lower prevalence of dental caries than normal population, but after adjusting the age of teeth eruption, there were only small and no significant difference between 2 groups.…”
Section: Dental Cariesmentioning
confidence: 99%